Oriented Study of Virtual Simulation to Improve Critical Thinking Skill in Physics Learning with Inquiry Model: Bibliometric Analysis - Rahmatta Thoriq Lintangesukmanjaya; Binar Kurnia Prahani; Dwikoranto; Lindsay N. Bergsma (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2025)
Objective: To analyze the potential of virtual simulation in improving critical thinking skills in physics learning. Analysis of findings globally can be a new breakthrough in creating efforts to implement digital-based and competent learning media in the 21st century today and in the future. Method: This study was conducted using bibliometric analysis methods and systematic reviews using bibliometric analysis. The use of these two methods is carried out in order to obtain in-depth analysis through qualitative and quantitative data. Results: Based on the research that has been conducted, it is known that the trend of physics learning research with virtual simulations in educational articles over the past 10 years has continued to increase every year with a drastic increase occurring as a reminder that the use of digital technology is increasingly needed. Novelty: In accordance with the findings of the bibliometric analysis, it was obtained that one of the experience-based learning that can be integrated with virtual simulation is the inquiry learning model. It is recommended for future researchers to integrate inquiry learning in physics with virtual simulation media to improve critical thinking skills according to the global trend in adapting innovative learning through interactive media.